2009
DOI: 10.1016/j.jcrs.2009.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ophthalmic nonsteroidal antiinflammatory drugs in suppressing anterior capsule contraction and secondary posterior capsule opacification

Abstract: Postoperative treatment with ophthalmic nonsteroidal antiinflammatory drug solutions prevented anterior capsule contraction and PCO in rabbit eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The bromfenac molecule has been evaluated extensively in Japan and the US 2734. Bromfenac sodium is designated chemically as sodium 2-amino-3-(4-bromobenzoyl) phenylacetate sesquihydrate, with an empirical formula of C 15 H 11 BrNNaO 3 · 1 ½ H 2 O 35.…”
Section: Chemical History Of Bromfenacmentioning
confidence: 99%
“…The bromfenac molecule has been evaluated extensively in Japan and the US 2734. Bromfenac sodium is designated chemically as sodium 2-amino-3-(4-bromobenzoyl) phenylacetate sesquihydrate, with an empirical formula of C 15 H 11 BrNNaO 3 · 1 ½ H 2 O 35.…”
Section: Chemical History Of Bromfenacmentioning
confidence: 99%
“…It remains unknown whether NSAID use for four (4) weeks translates into improved outcomes or overall comfort of the patient [ 13 , 14 ]. Studies have linked other benefits such as decreased capsular phimosis and miosis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this management regimen has been extended to include dosing prior to and on the day of surgery, to potentially improve analgesia, reduce intra- and postoperative inflammation, and to minimize the risk of postoperative complications 6. Bromfenac ophthalmic solution has been evaluated in numerous clinical studies in both Japan and the United States (US)714 and has been shown to be a potent inhibitor of cyclooxygenase (COX). The COX enzyme promotes prostaglandin synthesis by converting arachidonic acid into prostaglandin, a necessary component for the onset of inflammation 1519.…”
Section: Introductionmentioning
confidence: 99%